Clay surface characteristics using atomic force microscopy (2018)
The first component for the manufacture of masonry products used in construction is clay, which provides the plasticity that facilitates the molding and handling of the product. The second component is the feldspar in form of alumina (Al2O3) which is used as flux. The third one is silica (SiO2) which is used as a filling material and stabilizer. These elements are determined by chemical composition using fluorescence analysis or X-ray diffraction, which is the basis of the modern classification of minerals. Thereby, the main objective of this research is to study the surface characteristics of clay samples from an industrial company producing H-10 blocks in the region of Norte de Santander, by studying the surfaces of the samples selected through the analysis by Atomic Force Microscopy, in order to compare the results with those found in the literature, and at the same time taking into account the chemical elements in their highest composition. The results show that this is a technique that allows the identification of clay components, thus validating what has been found in physical and chemical analysis, expecting to provide a scientific contribution by AFM, because there is little information related to the characterization topography of clay materials.